2003
DOI: 10.1128/ec.2.6.1336-1349.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans Gene Expression during Experimental Cryptococcal Meningitis

Abstract: Cryptococcus neoformans, an encapsulated basidiomycete fungus of medical importance, is capable of crossing the blood-brain barrier and causing meningitis in both immunocompetent and immunocompromised individuals. To gain insight into the adaptation of the fungus to the host central nervous system (CNS), serial analysis of gene expression (SAGE) was used to characterize the gene expression profile of C. neoformans cells recovered from the CNS of infected rabbits. A SAGE library was constructed, and 49,048 tags… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 96 publications
6
119
0
1
Order By: Relevance
“…Trehalose is composed of two glucose molecules linked at their 1-carbons and is rapidly produced under various cellular stresses. Two recent studies have identified both trehalose and the expression of genes in its pathway at the sites of cryptococcal infections, and these results reinforce the potential importance of the trehalose pathway in C. neoformans survival within the host (28,50).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Trehalose is composed of two glucose molecules linked at their 1-carbons and is rapidly produced under various cellular stresses. Two recent studies have identified both trehalose and the expression of genes in its pathway at the sites of cryptococcal infections, and these results reinforce the potential importance of the trehalose pathway in C. neoformans survival within the host (28,50).…”
mentioning
confidence: 53%
“…First, in a global transcriptional gene analysis, CSF was removed from rabbits infected with cryptococcal meningitis. With the use of serial analysis of gene expression for identification and quantitation of transcripts from yeast cells within the CSF, one of the genes most highly expressed was TPS1 (50). Second, the potential importance of the trehalose pathway for the yeast within the central nervous system was further supported when tissues surrounding cryptococcomas from infected rat brains and lungs were analyzed by NMR studies (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…For strains that did not cause mortality of 50% or more within the 45-day timeframe of the experiment, we arbitrarily assigned an ST 50 of 55 days. system infection (16,17). Taken together, we propose that mitochondrial function is critical for the virulence of this lineage.…”
Section: Identification Of Genes Associated With Enhanced Intracellulmentioning
confidence: 97%
“…Within the small subset of four coregulated protein spots, we identified a homologue of CipC (UM03284), a small conserved fungal protein with unknown biological function. CipC was first identified as a concanamycin induced protein in Aspergillus nidulans and homologues have since been found to be induced under many different conditions: it is up-regulated during ectomycorrhizal symbiosis in Paxillus species, in experimental cryptococcal meningitis and by nitrogen starvation in Gibberella fujikuroi [26][27][28][29]. CipC is also significantly up-regulated under conditions of nitrogen starvation in U. maydis (M. Bölker, unpublished results).…”
Section: Proteins Up-regulated In Both B-and Rac1-dependent Filamentsmentioning
confidence: 99%